USING SOCIAL MEDIA AS A MARKETING TOOL FOR TRAVELLERS - Lompot, Mary Fatima D; Pomentil, Rodel C (PEOPLE: International Journal of Social Sciences, 2018)
This research assessed the influence of social media in the information search and decision-making processes of local leisure travelers working in the BPO (Business Process Outsourcing) industry in Metro Manila. It synthesized existing researches, concepts and theories to understand how social media applications influence local travelers. It also presented a snapshot of how consumers gather information and make decisions regarding their travel purchases in this rapidly increasing, commercialized field. Specifically, the paper described the socio-demographic profile of the travelers. It determined the social media sites most frequently used by travelers, the factors and elements that help in making their travel decisions, and the problems and issues they encountered. A profile comparison between social media and non-social media users was also made to determine if there was a significant difference between the two sets of respondents.